The development of ICT and its political impact in Malaysia - Rosyidah Muhammad (Penerbit Universiti Malaysia Sabah, 2015)
This study aims to identify the ways in which the Malaysian Government seeks to develop the country using Information Communication Technology (ICT) to be competitive in the globalization era. It is also aims to evaluate the extent of development of ICT ability to empower Malaysian community by enhance their participation in politics. Through ICT products, the community not only follows the development of ICT revolution but they also create a knowledge society and helps to boost the quality of life of communities by participating in politics. As such it enable the transformation of Malaysian politics especially in elections.